Synthesis of hydrogen storage materials in a Ti-Zr-Ni system using the hydride cycle technology during dehydrogenation by an electron beam in a vacuum - Dmytrenko, O.E.; Dubinko, V.I.; Borysenko, V.M.; Irwin, K. (Вопросы атомной науки и техники, 2020)
The synthesis of intermetallic material was carried out by means of dehydrogenating annealing of a (TiH₂)₃₀Zr₄₅Ni₂₅ sample in vacuum by an electron beam. The properties of the obtained material were studied for establishing the structural phase composition by scanning electron microscopy and X-ray structural analysis. It was found that prolonged exposure of an electron beam to a sample containing titanium hydride leads to a number of structural transformations in the material, accompanied by a redistribution of hydrogen from titanium to zirconium and culminating in the synthesis of a ternary alloy with characteristic growth structures. The processes of hydrogen sorption-desorption by a synthesized sample were studied, the temperature ranges of these processes and the absorption capacity of the obtained material were established. It was shown that the structure of the sample formed upon heating by an electron beam promotes the absorption of hydrogen at room temperature up to 1.41 wt.%. Проведено синтез інтерметалічного матеріалу за допомогою дегідруючого відпалу зразка (TiH₂)₃₀Zr₄₅Ni₂₅ у вакуумі електронним пучком. Методом скануючої електронної мікроскопії і рентгеноструктурного аналізу досліджені властивості отриманого матеріалу для встановлення структурно-фазового складу. Встановлено, що тривала дія електронного пучка на зразок, що містить гідрид титану, призводить до ряду структурних перетворень у матеріалі, що супроводжуються перерозподілом водню з титану в цирконій і завершуються синтезом потрійного сплаву з характерними структурами зростання. Досліджено процеси сорбціїдесорбції водню синтезованим зразком, встановлені температурні діапазони даних процесів і поглинальна здатність отриманого матеріалу. Показано, що сформована при нагріванні електронним пучком структура зразка сприяє поглинанню водню при кімнатній температурі до 1,41 ваг.%. Проведен синтез интерметаллического материала посредством дегидрирующего отжига образца (TiH₂)₃₀Zr₄₅Ni₂₅ в вакууме электронным пучком. Методом сканирующей электронной микроскопии и рентгеноструктурного анализа исследованы свойства полученного материала для установления структурнофазового состава. Установлено, что длительное воздействие электронного пучка на образец, содержащий гидрид титана, приводит к ряду структурных превращений в материале, сопровождающихся перераспределением водорода из титана в цирконий и завершающихся синтезом тройного сплава с характерными структурами роста. Исследованы процессы сорбциидесорбции водорода синтезированным образцом, установлены температурные диапазоны данных процессов и поглотительная способность полученного материала. Показано, что сформировавшаяся при нагреве электронным пучком структура образца способствует поглощению водорода при комнатной температуре до 1,41 вес.%.